An update of thin-toed gecko Tenuidactylus bogdanovi (Reptilia, Gekkonidae) population status in Odessa City, Ukraine - Krasylenko, Yu.А.; Kukushkin, O.V. (Збірник праць Зоологічного музею, 2017)
The new data regarding the current status of Bogdanov’s thin-toed gecko population in Odessa city are presented. A population density of lizards is relatively high. Fourteen individuals of T. bogdanovi (21.4 % of juveniles) were found at the “Moldavanka” historical district on an area of circa 3.75 hectares in late July — early August 2017. The positive dynamics of urban gecko’s population allows considering T. bogdanovi as naturalized adventive species — Turanian faunistic element in the fauna of Ukraine. The gecko’s population increase and steadily expands distributional area to several dozens of hectares, what was confirmed by indirect evidence. The scientific significance of only European population of T. bogdanovi is also highlighted. Photos of Bogdanov’s thin-toed gecko in its habitats in Odessa city are published for the first time. Представлены данные о современном состоянии популяции тонкопалого геккона Богданова в г. Одесса. Плотность населения ящериц достаточно высока. На рубеже июля и августа 2017 г. в историческом районе «Молдаванка» на площади около 3,75 га было выявлено четырнадцать особей T. bogdanovi (21,4 % этого числа составляли ювенилы). Положительная динамика городской популяции с полным на то основанием позволяет считать T. bogdanovi натурализовашимся адвентивным видом (туранский фаунистический элемент в фауне Украины). По косвенным признакам, геккон увеличивает численность и продолжает расширять область обитания, которая на сегодняшний день достигла нескольких десятков гектаров. Обсуждается научное значение единственной европейской популяции T. bogdanovi. Фотографии геккона Богданова в среде его обитания в черте г. Одесса публикуются впервые. Представлено відомості щодо сучасного стану популяції тонкопалого гекона Богданова в м. Одеса. Щільність населення ящірок є вельми високою. Наприкінці липня — на початку серпня 2017 року в історичному районі «Молдаванка» на ділянці площею близько 3,75 га було виявлено чотирнадцять особин T. bogdanovi, причому 21,4 % складали ювенільні особини. На основі позитивної динаміки міської популяції можна вважати T. bogdanovi натуралізованим адвентивним видом (туранський фауністичний елемент у фауні України). За непрямими ознаками, гекон збільшує чисельність і продовжує розширювати територію проживання, яка на сьогодні сягає кількох десятків гектарів. Обговорюється наукове значення єдиної в Європі популяції цього виду. Вперше опубліковано фотографії гекона Богданова в середовищі його існування в межах м. Одеса.